Dietary nitrate supplementation augments nitric oxide synthase mediated cutaneous vasodilation during local heating in healthy humans - Keen, Jeremy T. (Kansas State University, 2013)
Nitrate supplementation in the form of beetroot juice (BRJ) has been shown to increase nitric oxide (NO), where nitrate can be reduced to nitrite and NO through both nitric oxide synthase (NOS) independent and dependent pathways. We tested the hypothesis that BRJ would augment the NO component of cutaneous thermal hyperemia. Dietary intervention consisted of one shot of BRJ for three days. Six subjects were equipped with two microdialysis fibers on the ventral forearm and randomly assigned to lactated Ringer’s (control) or continuous infusion of 20mM L-NAME (NOS inhibitor). The control site was subsequently perfused with L-NAME once a plateau in the local heating response was achieved to quantify NOS-dependent cutaneous vasodilation. Skin blood flow via laser-Doppler flowmetry (LDF) and mean arterial pressure (MAP) were measured; cutaneous vascular conductance (CVC) was calculated as LDF/MAP and normalized to %CVCmax. Maximal vasodilation was achieved via local heating to 43°C and 54mM sodium nitroprusside infusion. There was a significant decrease in DBP after BRJ (Pre-BRJ:74 ± 1 mmHg vs. Post-BRJ: 61 ± 2 mmHg; p < 0.05) and significant reduction in MAP after BRJ (Pre-BRJ: 90 ± 1 mmHg vs. Post-BRJ: 80 ± 2 mmHg; p < 0.05). The initial peak and secondary plateau phase of cutaneous thermal hyperemia were attenuated at sites with continuous LNAME; however, there was no effect of BRJ on either the initial peak at control sites (Pre-BRJ: 76 ± 3%CVCmax vs. Post-BRJ: 75 ± 4%CVCmax) or L-NAME sites (Pre-BRJ: 60 ± 4%CVCmax vs. Post-BRJ: 59 ± 5%CVCmax) or the secondary plateau phaseat control sites (Pre-BRJ: 88 ± 4%CVCmax vs. Post-BRJ: 90 ± 4%CVCmax) or L-NAME sites (Pre-BRJ: 45 ± 5%CVCmax vs. Post-BRJ: 51 ± 3%CVCmax). The decrease in %CVCmax to L-NAME infusion during the plateau of local heating (i.e. post-L-NAME drop) was greater after BRJ (Pre-BRJ: 36 ± 2%CVCmax vs. Post-BRJ: 28 ± 1%CVCmax; p < 0.05). This resulted in a greater contribution of NOS to the plateau phase of local heating (Pre-BRJ: 57±3%CVCmax vs. Post-BRJ: 64±2%CVCmax; p < 0.05). These data suggest BRJ modestly improves NOS-dependent vasodilation to local heating in the cutaneous vasculature of healthy humans.
Keywords: Nitric oxide; Nitric oxide synthase; Kinesiology (0575)